Preparation method of bimetallic monatomic porphyrin metal organic framework catalyst and application of bimetallic monatomic porphyrin metal organic framework catalyst
By preparing bimetallic monoatomic porphyrin metal organic framework catalyst, the problem of difficult to achieve the small unit area and nanoscale thickness of traditional metal organic framework materials is solved, and the effect of efficient removal of phenolic pollutants in water in advanced oxidation processes is achieved.
Patent Information
- Application Number
- CN202411699409.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
The traditional sheet metal organic framework material has a small unit area and is difficult to achieve nanoscale thickness, which limits its application efficiency in advanced oxidation processes.
The preparation method of bimetallic monoatomporphyrin metal organic framework catalyst is adopted, and the N,N-dimethylformamide ethanol metal solution is formed by mixing Fe(NO3)3·9H2O, Co(NO3)2·6H2O, formic acid and polyvinylpyrrolidone. After heating of an autoclave and high-speed centrifugation, a catalyst with a stable structure and a monolayer thickness of about 0.5 nm was finally obtained.
This catalyst can efficiently remove phenolic pollutants in water in the advanced oxidation process of sulfate radicals, and has a wide pH application range and efficient degradation ability.
Smart Images

Figure CN119529304A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of a catalyst, in particular to a preparation method of a bimetallic single-atom porphyrin metal organic framework catalyst and application of the catalyst. Background Art
[0002] In recent years, advanced oxidation processes have been widely used in the field of degradation of organic pollutants. Advanced oxidation processes based on sulfate free radicals have broad application prospects in the field of environmental remediation due to their technical advantages such as fast and efficient reaction, superior effect in degrading organic pollutants, and wide pH adaptability. In view of the limitations of traditional oxidation technology in treating organic pollutants, such as low efficiency and difficulty in removing complex organic pollutants, advanced oxidation processes have developed and have been effectively applied to the treatment of high-concentration organic wastewater. Advanced oxidation process is a free radical-based reaction. Because it can produce a variety of free radicals during the reaction, such as hydroxyl radicals, sulfate radicals and superoxide anion radicals, these free radicals have the characteristics of fast reaction rate and strong oxidation ability and have been widely used in engineering. Permonosulfate is a new type of inorganic sulfate oxidant. As SO4 ·– It is a good precursor for the production of pollutants, and it shows better performance than peroxydisulfate and sulfite in the degradation of pollutants. When using peroxymonosulfate as a chemical oxidant, it can be activated in a variety of ways to produce free radicals, thereby achieving efficient degradation of organic pollutants. Heat, alkali, metal ions, radiation and other methods can all cause the molecules inside peroxymonosulfate to break and generate free radicals with high oxidizing properties. Among them, due to the use of heterogeneous catalysts for catalytic activation, it has become a hot topic in the research field because of its simple preparation, low energy consumption and high activation efficiency.
[0003] Metal-organic framework materials are widely used in the treatment of organic wastewater using advanced oxidation processes due to their large unit area, nanometer-scale thickness, and adjustable active site centers. However, the small unit area and difficulty in achieving nanometer-scale thickness of traditional sheet-like metal-organic framework materials remain potential obstacles to the industrialization of metal-organic framework materials today.
[0004] The applicant has not found any literature reports in the prior art that are identical or similar to the present invention. Summary of the invention
[0005] The invention discloses a preparation method of a bimetallic single-atom porphyrin metal organic skeleton catalyst and application of the catalyst. The bimetallic single-atom porphyrin metal organic skeleton catalyst prepared by the invention can efficiently remove phenol pollutants in water.
[0006] The overall technical concept of the present invention is:
[0007] The preparation method of the bimetallic single-atom porphyrin metal organic framework catalyst is characterized by comprising the following steps:
[0008] A. Fe(NO3)3·9H2O:Co(NO3)2·6H2O:formic acid:polyvinylpyrrolidone is mixed in a molar ratio of 55.56:55.56:5.89:1 as a solute, and an N,N-dimethylformamide ethanol metal solution of not less than 12 ml is prepared in a molar ratio of solute:solution equal to 1:15.45, wherein the solution is mixed in a volume ratio of N,N-dimethylformamide:ethanol of 3:1;
[0009] B. Add 4.4 mg of (4-carboxyphenyl)-porphyrin, 3 ml of N,N-dimethylformamide, 1 ml of ethanol, and 6 ml of the N,N-dimethylformamide ethanol metal solution prepared in step A into an autoclave, stir at room temperature for 10 minutes, and heat the mixture at 80° C. for 6 hours;
[0010] C. After high-speed centrifugation of the heated mixture in step B, wash it three times with ethanol, then wash it with water, dry it, and grind it to obtain a brown bimetallic single-atom porphyrin metal organic framework catalyst.
[0011] The specific technical concept of the present invention also includes:
[0012] The preparation of (4-carboxyphenyl)-porphyrin in step B belongs to the prior art, and the applicant will not repeat it. It is preferably prepared by the method described in "Freestanding Millimeter-Scale Porphyrin-Based Monoatomic Layers with 0.28nmThickness for CO2 Electrocatalysis" (Deren Yang, Shouwei Zuo, Haozhou Yang, YueZhou, and Xun Wang*; anie_202006899_sm_miscellaneous_information.pdf).
[0013] In order to achieve better centrifugation effect, the preferred technical implementation method is that the high-speed centrifugation condition in step C is centrifugation at a speed of 8000 rpm for 3 minutes.
[0014] In order to better elute impurities in the product, the preferred technical implementation means is that the water washing in step C is washed three times with deionized water and then washed three times with pure water.
[0015] To ensure the drying effect, the preferred technical implementation means is that the drying in step C is carried out at a temperature of 60° C. for 4 hours.
[0016] In order to ensure a better catalytic degradation effect, the preferred technical means is that the catalytic system in the sulfate radical advanced oxidation process adopts a peroxymonosulfate system, and the pH value is 3-9.
[0017] The essential features and technical advances of the present invention are:
[0018] 1. The metal organic framework material prepared by the present invention has a stable structure and can efficiently load metal iron and cobalt.
[0019] 2. Since the monolayer thickness of the bimetallic single-atom porphyrin metal-organic framework catalyst is about 0.5nm and the structure is uniform, it effectively ensures the utilization of catalytic sites and also promotes the uniformity of the catalytic pathway, thereby improving the selectivity of specific products.
[0020] 3. The process of preparing the catalyst of the present invention is simple to operate, the process is green and environmentally friendly, and the prepared product is an environmentally friendly material.
[0021] 4. The bimetallic single-atom porphyrin metal organic framework catalyst prepared by the present invention can be used in the sulfate radical advanced oxidation process to effectively degrade phenol pollutants in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings of the present invention include:
[0023] Figure 1 Transmission electron microscopy images of the products prepared in Examples 1 and 2.
[0024] Wherein a, b are the transmission electron microscope images of the bimetallic single atom porphyrin metal organic skeleton catalyst prepared by embodiment 1, from a it can be seen that the typical lamella structure of the bimetallic single atom porphyrin metal organic skeleton catalyst is several layers of thin layers stacked together, and it is transparent, indicating that the number of stacked layers is less, and the color is uniform, and impurities are few. From b it can be seen that the bimetallic single atom porphyrin metal organic skeleton catalyst has partial wrinkles, which illustrates that the bimetallic single atom porphyrin metal organic skeleton catalyst inevitably reunites in a small part in the preparation process, and this small-scale reunion phenomenon will not change the overall morphology characteristics of PML-Fe-Co, and the overall structure still shows as nano-sheet structure. C, d are the transmission electron microscope images of the monometallic single atom porphyrin metal organic skeleton catalyst prepared by embodiment 2. From c, d it can be seen that the monometallic single atom porphyrin metal organic skeleton catalyst presents wrinkles, which illustrates that the monometallic single atom porphyrin metal organic skeleton catalyst has completely reunited. The bimetallic active sites of iron and cobalt are evenly dispersed on the nanosheet structure. Therefore, the application effect of the bimetallic single-atom porphyrin metal-organic framework catalyst is better than that of the monometallic single-atom porphyrin metal-organic framework catalyst.
[0025] Figure 2The X-ray diffraction analysis spectra of the products prepared in Examples 1 to 4 are shown.
[0026] Wherein a is the X-ray diffraction analysis spectrogram of the bimetallic single-atom porphyrin metal organic skeleton catalyst prepared in Example 1, and b is the X-ray diffraction analysis spectrogram of the monometallic single-atom porphyrin metal organic skeleton catalyst prepared in Example 2. C is the X-ray diffraction analysis spectrogram of Co3O4 and Fe3O4 prepared in Examples 3 and 4. From a and b, it can be seen that the bimetallic single-atom porphyrin metal organic skeleton catalyst and the monometallic single-atom porphyrin metal organic skeleton catalyst have no peaks, indicating that both materials are amorphous materials. From c, it can be seen that ferroferric oxide and cobalt trioxide have peaks, corresponding to JCPDS NO.26-1136 ferroferric oxide standard card and JCPDS NO.71-2450 cobalt trioxide standard card, which are all crystalline materials.
[0027] Figure 3 This is a diagram showing the efficiency of catalytic degradation of acetaminophen by different systems in Example 3.
[0028] Wherein a is the efficiency diagram of acetaminophen degradation by different contrast catalysts of bimetallic single-atom porphyrin metal organic framework catalysts. From a, it can be seen that a single catalyst cannot degrade acetaminophen, which shows that the bimetallic single-atom porphyrin metal organic framework catalyst cannot adsorb and degrade acetaminophen. The degradation effects of crystalline materials ferric oxide and cobalt oxide are not as good as those of amorphous bimetallic single-atom porphyrin metal organic framework catalysts. PML-Fe is also not as good as bimetallic single-atom porphyrin metal organic framework catalysts due to agglomeration. b is the efficiency diagram of acetaminophen degradation by different contrast pH of bimetallic single-atom porphyrin metal organic framework catalysts. From b, it can be seen that the bimetallic single-atom porphyrin metal organic framework catalyst can degrade acetaminophen under strong acid, weak acid, neutral, weak base and strong base conditions, which shows that the pH application range of bimetallic single-atom porphyrin metal organic framework catalysts is wide. c is the efficiency diagram of the degradation of acetaminophen by different comparative catalytic systems of bimetallic single-atom porphyrin metal organic framework catalysts. From c, it can be seen that the bimetallic single-atom porphyrin metal organic framework catalyst can degrade acetaminophen in sulfite, peroxymonosulfate, and peroxydisulfate systems, which shows the universality of bimetallic single-atom porphyrin metal organic framework catalysts in catalytic systems. d is the efficiency diagram of the degradation of acetaminophen by bimetallic single-atom porphyrin metal organic framework catalysts in different water qualities. From d, it can be seen that the bimetallic single-atom porphyrin metal organic framework catalyst can efficiently degrade acetaminophen in both tap water and laboratory-prepared simulated urban wastewater. This shows that the bimetallic single-atom porphyrin metal organic framework catalyst will play a great advantage in treating actual wastewater.
[0029] Figure 4This is the atomic force microscope spectrum of the bimetallic single-atom porphyrin metal organic framework catalyst. Figure 4 It can be seen that the monolayer thickness of the bimetallic single-atom porphyrin metal-organic framework catalyst is about 0.5 nanometers.
[0030] Figure 5 The high-resolution transmission electron microscopy image and EDS-Mapping spectrum of the bimetallic single-atom porphyrin metal organic framework catalyst are shown in the figure. It can be seen from the figure that the porphyrin metal framework metal organic framework material is efficiently loaded with iron and cobalt atoms. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with embodiments, but it should not be construed as limiting the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims, and any replacement of equivalent technical means made according to the description shall not depart from the protection scope of the present invention.
[0032] Example 1
[0033] The preparation method of the bimetallic single-atom porphyrin metal organic framework catalyst comprises the following steps:
[0034] A. 0.005 mol of Fe(NO3)3·9H2O, 0.005 mol of Co(NO3)2·6H2O, 0.00053 mol of formic acid and 0.000090 mol of polyvinylpyrrolidone were mixed as solutes, and 12 ml of N,N-dimethylformamide ethanol metal solution was prepared in a molar ratio of solute to solution equal to 1:15.45. The 12 ml solution was mixed in a ratio of N,N-dimethylformamide to ethanol in a volume ratio of 3:1;
[0035] B. Add 4.4 mg of (4-carboxyphenyl)-porphyrin, 3 ml of N,N-dimethylformamide, 1 ml of ethanol, and 6 ml of the N,N-dimethylformamide ethanol metal solution prepared in step A into an autoclave, stir at room temperature for 10 minutes, and heat the mixture at 80° C. for 6 hours;
[0036] C. The mixture heated in step B was centrifuged at 8000 rpm for 3 minutes, washed three times with ethanol, three times with deionized water, and three times with pure water. After drying at 60° C. for 4 hours, the mixture was ground to obtain a brown bimetallic single-atom porphyrin metal organic framework catalyst.
[0037] The (4-carboxyphenyl)-porphyrin in step B is prepared by the following method:
[0038] a. Preparation of (4-carboxyphenyl)-porphyrin intermediate
[0039] a1. 3.0 g of pyrrole, 6.9 g of methyl paraformylbenzoate and 100 ml of propionic acid were sequentially added into a 500 ml three-necked flask, and the mixture was placed in an oil bath at 90° C. for 12 hours, and condensed under reflux for 12 hours to obtain a (4-carboxyphenyl)-porphyrin intermediate.
[0040] a2. Wash the (4-carboxyphenyl)-porphyrin intermediate in a1 three times with methanol, ethyl acetate and tetrahydrofuran respectively;
[0041] a3, drying the washed intermediate product under vacuum at 35°C to obtain a (4-carboxyphenyl)-porphyrin intermediate product;
[0042] b. Preparation of (4-carboxyphenyl)-porphyrin
[0043] b1. Place 0.75 g of (4-carboxyphenyl)-porphyrin intermediate, 50 ml of tetrahydrofuran-methanol, and 25 ml of 46.95 mmol / L potassium hydroxide aqueous solution in a 500 ml three-necked flask, place in an oil bath at 90° C. for 12 hours, and then reflux under condensation for 12 hours;
[0044] b2. The reactant in step b1 was evaporated to a nearly wet state under oil bath conditions, 100 ml of pure water was added, and a 1 mol / l hydrochloric acid solution was added dropwise until no precipitate was formed, and the green precipitate was collected, washed three times with clean water and dried in vacuo at 60° C. to obtain (4-carboxyphenyl)-porphyrin.
[0045] Example 2
[0046] The difference between this embodiment and embodiment 1 is that in step A of catalyst preparation, 0.01 mol of Fe(NO3)3·9H2O, 0.00053 mol of formic acid and 0.000090 mol of polyvinyl pyrrolidone are mixed as solutes. The prepared catalyst is a monometallic monoatom porphyrin metal organic framework catalyst.
[0047] The rest of the contents are the same as in Example 1.
[0048] Example 3
[0049] Cobalt hydroxide was prepared by adding ammonia water dropwise to cobalt nitrate hexahydrate using a precipitation method, and the temperature was raised to 500°C at a heating rate of 4°C / min in a muffle furnace, and then kept at this temperature for 120 minutes to obtain Co3O4.
[0050] Example 4
[0051] Cobalt hydroxide was prepared by adding ammonia water dropwise to ferric nitrate nonahydrate by a precipitation method, and the temperature was raised to 500°C at a heating rate of 4°C / min in a muffle furnace, and then kept at this temperature for 120 minutes to obtain Fe3O4.
[0052] Example 5
[0053] 1. Impact of different contrast catalysts
[0054] The catalytic degradation of acetaminophen by different materials showed that the content of acetaminophen remained almost unchanged under the condition that only peroxymonosulfate and acetaminophen pollutants were present. For the bimetallic single-atom porphyrin metal organic framework catalyst prepared in Example 1, the adsorption effect of acetaminophen was investigated under the condition that there was no peroxymonosulfate, and acetaminophen was hardly adsorbed. Figure 3 In a, it can be found that the degradation efficiency of acetaminophen in 10 minutes is 100%. The efficiency of catalytic activation of peroxymonosulfate to degrade acetaminophen prepared by the single metal single atom porphyrin metal organic framework catalyst of embodiment 2 is very limited, and the degradation efficiency in 10 minutes is 26.5%. Co3O4 and Fe3O4 also have the ability of certain activation peroxymonosulfate to degrade acetaminophen. The degradation efficiency of Co3O4 in 10 minutes is 59.5%, and the degradation efficiency of Fe3O4 in 10 minutes is 10%.
[0055] 2. Effect of different pH
[0056] The bimetallic single-atom porphyrin metal organic framework catalyst prepared in Example 1 catalyzes the degradation of acetaminophen at different pH values. At pH=3, the efficiency of acetaminophen degradation within 10 minutes is 83.5%. At pH=5, the degradation efficiency within 10 minutes is 86.0%, and at pH=7, the degradation efficiency within 10 minutes is 100%. At pH=9, the degradation efficiency within 10 minutes is 93.0%. At pH=11, the degradation efficiency within 10 minutes is 60.5%.
[0057] 3. Influence of different catalytic systems
[0058] The bimetallic single-atom porphyrin metal organic framework catalyst prepared in Example 1 was used to catalyze the degradation of acetaminophen using different catalytic systems. Figure 3 At pH=7, the efficiency of acetaminophen degradation in 10 minutes under sulfite system is 58.5%, the efficiency of acetaminophen degradation in 10 minutes under peroxydisulfate system is 67.1%, and the efficiency of acetaminophen degradation in 10 minutes under peroxymonosulfate system is 100%.
[0059] 4. Impact of different water quality
[0060] The bimetallic single-atom porphyrin metal organic framework catalyst prepared in Example 1 was used to catalyze the degradation of acetaminophen in three different water qualities: tap water, ultrapure water, and simulated urban wastewater. Figure 3 It can be seen from Figure d that the efficiency of acetaminophen degradation within 10 minutes is 100% in the three water qualities.
[0061] 5. Simulate urban wastewater preparation
[0062] The simulated urban wastewater in the present invention refers to "Modulating the electron structure of Co-3din Co3O 4-x / WO 2.72 The parameters of the two papers "for boosting peroxymonosulfate activation and degradation ofsulfamerazine: Roles of high-valence W and rich oxygen vacancies" and "Regulating the Co 3d center of Co3O4 by Co3O4 / g-C3N4 to enhance electronic activity forsulfamethizole effectively degaradtion by permonosulfate activation" were prepared, and the preparation ingredients are shown in Table 1.
[0063]
[0064]
Claims
1. A method for preparing a bimetallic single-atom porphyrin metal organic framework catalyst, characterized in that The steps include: A. Fe(NO3)3·9H2O:Co(NO3)2·6H2O:formic acid:polyvinylpyrrolidone is mixed in a molar ratio of 55.56:55.56:5.89:1 as a solute, and an N,N-dimethylformamide ethanol metal solution of not less than 12 ml is prepared in a molar ratio of solute:solution equal to 1:15.45, wherein the solution is mixed in a volume ratio of N,N-dimethylformamide:ethanol of 3:1; B. Add 4.4 mg of (4-carboxyphenyl)-porphyrin, 3 ml of N,N-dimethylformamide, 1 ml of ethanol, and 6 ml of the N,N-dimethylformamide ethanol metal solution prepared in step A into an autoclave, stir at room temperature for 10 minutes, and heat the mixture at 80° C. for 6 hours; C. After high-speed centrifugation of the heated mixture in step B, wash it three times with ethanol, then wash it with water, dry it, and grind it to obtain a brown bimetallic single-atom porphyrin metal organic framework catalyst.
2. The method for preparing a bimetallic single-atom porphyrin metal organic framework catalyst according to claim 1, characterized in that The high-speed centrifugation condition in step C is centrifugation at a speed of 8000 rpm for 3 minutes.
3. The method for preparing a bimetallic single-atom porphyrin metal organic framework catalyst according to claim 1, characterized in that The washing with water in step C is washing three times with deionized water and then washing three times with pure water.
4. The method for preparing a bimetallic single-atom porphyrin metal organic framework catalyst according to claim 1, characterized in that The drying in step C is carried out at a temperature of 60° C. for 4 hours.
5. Application of bimetallic single-atom porphyrin metal organic framework catalyst in the sulfate radical advanced oxidation process for degradation of phenolic pollutants in water, characterized in that The catalytic system in the sulfate radical advanced oxidation process adopts a sulfite system, a peroxydisulfate system or a peroxymonosulfate system, and the pH value is 3-11.
6. The use according to claim 5, characterized in that The catalytic system in the sulfate radical advanced oxidation process adopts a peroxymonosulfate system, with a pH of 3-9.